Macrophage activation syndrome in systemic juvenile idiopathic arthritis - Masaki Shimizu (Immunological Medicine, 2021)
Macrophage activation syndrome (MAS) is a severe, potentially life-threatening complication of systemic juvenile idiopathic arthritis (s-JIA). An immunological feature is the excessive activation and proliferation of T lymphocytes and macrophages. Massive hypercytokinemia is strongly associated with its pathogenesis, particularly the overproduction of interleukin (IL)-1, IL-6 and IL-18; interferon (IFN)-γ; and tumor necrosis factor (TNF)-α. Furthermore, heterozygous mutations in causative genes for primary hemophagocytic lymphohistiocytosis and in vivo exposure to highly elevated levels of IL-6 and IL-18 might induce natural killer cell dysfunction and decrease their numbers, respectively. A proper diagnosis is important to begin appropriate therapeutic interventions and change an unfavorable prognosis. The 2016 ACR/EULAR classification criteria for MAS have a high diagnostic performance; however, the diagnostic sensitivity for onset is relatively low. Therefore, careful monitoring of laboratory values during the course of MAS is necessary to diagnose it early in s-JIA. Further studies on the diagnosis and monitoring of disease activity using serum cytokine profile and a targeted cytokine strategy are required.